Perilaku Menyikat Gigi terhadap Oral Hygiene Anak Sekolah - Langgeng Setyo Nugroho; Dian Femala; Yeni Maryani (Poltekkes Kemenkes Kupang, 2019)
Abstract: Teeth Brushing Behavior of School Children's Oral Hygiene. Data obtained at SDN 60 Kubu Raya Regency has no UKGS (School Dental Health Business) program. The condition of the teeth beforehand will affect the development of dental health in later adulthood. The causes of dental health problems in children include behavioral factors and attitudes ignoring dental hygiene. The study aims to determine the behavior of brushing teeth against oral hygiene in grade IV elementary school children in SDN 60 Kubu Raya Regency. This research is an analytic type of research. Data is processed in the form of frequency distributions and statistical tests using Chi-Square. The population in this study amounted to 40 people. Samples were taken using a total sampling technique of 40 respondents. Based on the results of research in SDN 60 Kubu Raya Regency that female respondents were 23 (57.5%), the respondents aged 9 years were 18 (45%), based on the technique of brushing teeth respondents were categorized as moderate as 21 (52.5%), respondents brushed at the wrong time 33 (82.5%), according to the frequency of brushing their teeth, they brushed their teeth twice a day as many as 24 (60%), while for OHI-S respondents were of medium and bad category as many as 17 (42.5%). It was concluded that there was an effect of technique, time and frequency of tooth brushing on oral hygiene of grade IV elementary school students of SDN 60, Kuburaya Regency. Abstrak: Perilaku Menyikat Gigi terhadap Oral Hygiene Anak Sekolah. Data yang diperoleh di SDN 60 Kabupaten Kubu Raya belum ada program UKGS (Usaha Kesehatan Gigi Sekolah). Keadaan gigi sebelumnya akan berpengaruh terhadap perkembangan kesehatan gigi pada usia dewasa nanti. Penyebab timbulnya masalah kesehatan gigi pada anak diantaranya adalah faktor perilaku dan sikap mengabaikan kebersihan gigi. Penelitian bertujuan untuk mengetahui perilaku menyikat gigi terhadap oral hygiene anak sekolah dasar kelas IV di SDN 60 Kabupaten Kubu Raya. Penelitian ini merupakan penelitian jenis analitik. Data diolah dalam bentuk distribusi frekuensi dan di uji statistik menggunakan Chi-Square. Populasi dalam penelitian ini berjumlah 40 orang. Sampel diambil menggunakan teknik total sampling yang berjumlah 40 responden. Berdasarkan hasil penelitian di SDN 60 Kabupaten Kubu Raya bahwa responden perempuan sebanyak 23 (57,5%), pada respondenberumur 9 tahun sebanyak 18 (45%), berdasarkan teknik menyikat gigi responden berkategori sedang sebanyak 21 (52,5%), responden menyikat gigi pada waktu yang tidak tepat sebanyak 33 (82,5%), menurut frekuensi menyikat gigi responden menyikat gigi 2 kali sehari sebanyak 24 (60%), untuk OHI-S responden berkategori sedang dan buruk sebanyak 17 (42,5%). Disimpulkan bahwa terdapat pengaruh teknik, waktu dan frekuensi menyikat gigi terhadap oral hygiene anak sekolah dasar kelas IV SDN 60 Kabupaten Kuburaya.